Time-varying fair queueing scheduling for multicode CDMA based on dynamic programming. - Stamoulis, A. (IEEE Transactions on wireless communications)
Fair queueing (FQ) algorithms, which have been proposed for quality of service (QoS) wireline/wireless networking, rely on the fundamental idea that the service rate allocated to each user is proportional to a positive weight. Targeting wireless data networks with a multicode CDMA-based physical layer, we develop FQ with time-varying weight assignment in order to minimize the queueing delays of mobile users. Applying dynamic programming, we design a computationally efficient algorithm which produces the optimal service rates while obeying 1) constraints imposed by the underlying physical layer and 2) QoS requirements. Furthermore, we study how information about the underlying channel quality can be incorporated into the scheduler to improve network performance. Simulations illustrate the merits of our designs.